Dampak QRIS terhadap Kedaulatan Digital Indonesia dan Hubungan Perdagangan Internasional - Pitri Yani Pitri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
QRIS (Quick Response Code Indonesian Standard) is a national digital payment innovation launched by Bank Indonesia to strengthen Indonesia’s digital and economic sovereignty. By integrating various payment platforms into a single QR code standard, QRIS simplifies domestic transactions—especially for Micro, Small, and Medium Enterprises (MSMEs)—while reinforcing state control over financial infrastructure and data flows. This policy reduces reliance on international payment networks such as Visa and Mastercard, which previously dominated digital transactions and stored data abroad. On a global scale, QRIS functions as a tool of digital economic diplomacy through cross-border payment initiatives like ASEAN Pay, enabling Indonesia to expand its influence in the global digital payment ecosystem. However, the United States has criticized QRIS, arguing that it restricts access for foreign companies and poses a barrier to trade. In response, the Indonesian government asserts that QRIS is designed to protect national interests while promoting fair international collaboration. This study employs a normative juridical and descriptive qualitative approach to analyze QRIS-related regulations, its impact on digital sovereignty, and its implications for international trade relations. Secondary data is sourced from literature studies and official documents. The findings reveal that QRIS plays a vital role in accelerating MSME digital transformation, enhancing financial inclusion, and strengthening Indonesia’s bargaining position in global digital finance. Ultimately, QRIS stands not only as a transaction tool but also as a strategic symbol of Indonesia’s digital independence and competitiveness in the international financial landscape.